Implementasi Fatwa DSN-MUI No. 85/ DSN-MUI/XII/2012 Tentang Waad pada Akad Ijarah Muntahiya Bittamlik di BMI Makassar - Muh. Ihsan Dahri; Rahman Ambo Masse; Fadli Andi Natsif (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Banking functions primarily as an intermediation institution that collects and channels funds as credit. Sharia Banks guarantee Sharia compliance in every transaction. Among their activities is ijarah financing and its derivative, Ijarah Muntahiya Bittamlik (IMBT). This research aims to: (1) Understand the concept of waad in the MUI Fatwa and the IMBT contract at Bank Muamalat; (2) Assess the suitability of the MUI fatwa regarding waad on IMBT at Bank Muamalat; (3) Identify challenges and obstacles to implementing the fatwa. This field research, conducted at Bank Muamalat Indonesia's Makassar Branch, employs normative and qualitative methods. Findings reveal that the waad concept in the MUI fatwa is binding and must be implemented if conditions are met, and this applies to IMBT contracts at Bank Muamalat. The IMBT implementation aligns with MUI Fatwa principles and the Financial Services Authority. Challenges include limited public knowledge, fluctuating costs, and customer apathy. The research provides insights and implications for Islamic banking and its customers, serving as a reference for practitioners, policymakers, and researchers. It encourages future research to explore alternative methodologies, enhancing the body of knowledge and yielding more robust outcomes.